Do Vulnerable Youth Dream Of Precarious Employment? Decision Making at (In/Ex) clusion Pathways - Horcas López, Vicent; Bernad i Garcia, Joan Carles; Martínez Morales, Ignacio (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
This work analyses young people’s discourses characterized by problematic educational tracks, and who have been part of “second opportunity itineraries”. Based on interviews to the young, we try to understand the arguments they use to make sense of their own academic itineraries and the key decisions they have taken in this process. Their arguments highly relate with the actor’s social position, and are influenced by agents such as the family and the educational institution. Within this framework, youngsters construct expectations for the future. These expectations follow three different paths: low-qualified and precarious work arenas, which remain functional in the productive system’s context; protected settings with high dependency levels; and marginal paths which takes them to proximity networks with high vulnerability. These tracks show the tension between social reproduction and resistance.